Efficiency Concepts and Models that Evaluates the Strength of Concretes Containing Different Supplementary Cementitious Materials - Rahul Biswas; Baboo Rai (Civil Engineering Journal, 2019)
The usage of Supplementary Cementitious Materials (SCM) is very much acknowledged due to the several improvements possible in the concrete composites, and because of the general economy. Research work till date suggests that utilization of SCMs enhance a significant number of the performance characteristics of the hardened concrete. The idea of efficiency can be utilized for comparing the relative performance of different pozzolans when incorporated into concrete. The efficiency concept, which was initially developed for fly ash, can be effortlessly connected to other advantageous s as well, such as silica fume, slag and natural pozzolans. A quantitative understanding of the efficiency of SCMs as a mineral admixture in concrete is essential for its effective utilization. The paper reviews the literature pertaining to the different efficiency concepts and models present to date that evaluates the strength of concretes containing different SCMs. This short survey demonstrates that there is a need for a superior comprehension of the SCMs in concrete for its powerful usage. Also, it is an effort directed towards a specific understanding of the efficiency of SCMs in concrete.